Regional Competitiveness: Infrastructure, Education, And Health Sectors Approach - Moh. Khusaini; Yenny Kornitasari; Atu Bagus Wiguna; Murniati Murniati; Firdaus Finuliyah (Journal of International Conference Proceedings, 2022)
This study aims to analyze the effect of the infrastructure, education, and health sectors on regional competitiveness. This is because the government expenditures have been allocated to develop infrastructure, education, and health sectors in each region. In line with the principle of fiscal decentralization to increase services in the public sector. When the government increases the quality of public sectors, it can impact economic growth, social welfare, and regional competitiveness or in the economic developments component. Previous studies show that the government expenditures on the infrastructure and component of the human capital index can increase the economic development in each region. In line with the theory of expenditures by Musgrave, Rostow, and Adolf Wagner. Therefore, using a regression panel data with the secondary data. The result of this study shows the effect of infrastructure, education, and health sectors on the regional competitiveness, study case in the Indonesia Province. Based on this study, it implies that when the local government will increase the competitiveness index, they should allocate more expenditures on this component. Keywords: Regional Competitiveness, Infrastructure, Education, Health Sector